Možnosti využití flexibility v energetických společenstvích - Kubíčková, Klára (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2024)
Diplomová práce přináší rešerši nastavení legislativy pro energetická společenství na území České republiky, aktuální podmínky a očekávaný vývoj v poskytování a vyhodnocování flexibility. Práce též zmiňuje navrhované změny tarifní struktury a možné přístupy rozúčtování pro energetická společenství. Dále jsou v práci zmíněny možnosti zapojení flexibility v energetických společenstvích především z pohledu vyhodnocení poskytování flexibility. Na základě aktuálního legislativního nastavení a potenciálu výroben jsou zvolena modelová společenství, pro která je vyhodnoceno sdílení dle alokačních klíčů a návratnost.

The thesis presents a research of the legislative setting for energy communities in the Czech Republic, current conditions and expected developments in the provision and evaluation of flexibility. The thesis also deals with the proposed changes in the tariff structure and possible approaches to accounting for energy communities. Furthermore, the possibilities of flexibility involvement in energy communities, especially from the perspective of evaluation of flexibility provision are mentioned. Based on the current legislative setting and the potential of power stations, model communities are selected for which electricity sharing according to allocation keys and payback are evaluated.
Opportunities for flexibility in energy communities
Keywords: energetická společenství v ČR; flexibilita v elektroenergetice; změny tarifní struktury; agregace; energy communities in the Czech Republic; flexibility in the electricity sector; changes in tariff structure; aggregation